Pengembangan Evaluasi Pembelajaran Fisika Materi Teori Atom - Barus, Carolina Sri Athena; Sapulete, Heppy; Nirahua, Juliana (Physikos: Journal of Physics and Physics Education, 2023)
The purpose of this research is to develop a product in the form of an evaluation model of the physics learning process on atomic theory material that is suitable for use by students. The method used in this study is the Research and Development (R & D) method. The research subjects consisted of 22 students at the fifth-semester level in the Physics Education Study Program, at Pattimura University. The data was collected, namely through test sheets and observation sheets. Based on the trial results, all the instruments used in this study had a good model fit. This is because construct validity and reliability meet academic requirements. Meanwhile, the results of assessments from practitioners and users stated that the evaluation model of the physics learning process in atomic theory material for modern physics courses and learning outcomes was quite effective to apply.